Revolutionary Warfare? Assessing the Character of Competing Factions within the Boko Haram Insurgency. Issue 3 (2nd October 2019) - Stoddard, Edward
ABSTRACT: The respective politico-military characters of the competing factions within the Boko Haram insurgency have not received as much academic attention as other features of the Boko Haram phenomenon. This article uses the concept of "revolutionary warfare" to examine and compare the two main factions. Traditionally applied to Marxist movements, this conceptualization is increasingly associated with violent Jihadist groups who combine a revolutionary ideology with a strategy based on winning popular support and a growing ability to militarily beat conventional forces. It argues that the "Islamic State West Africa Province" faction has adopted a revolutionary warfare approach based on increasingly sophisticated semi-conventional warfare and a simultaneous drive to win popular support. The Jama'at Ahl as-Sunnah lid-Da'wah wa'l-Jihad faction, while equally revolutionary in its goals, appears, for doctrinal reasons and due to pressure from the military, to be operating in contrast to key revolutionary warfare precepts.